Semantic Complex of Travel in Work of A. G. Bitov - E. A. Mohammed Adam; A. G. Kovalenko (Научный диалог)
The semantic complex of travel in the work of Andrey Bitov is analyzed. It has been proven that the range of the writer’s travelers is very wide; they correlate with each other. The authors state that, in a broad sense, A. Bitov’s literary travels add up to an extensive travel catalogue, which presents all kinds of embodiment of artistic space and time. In addition, the writer’s work is viewed as the embodiment of the vector of movement in the “space of freedom”, as the space of “longing for culture.” Particular attention is paid to a cycle of stories about the Soviet republics, where important tools for the writer to create the image of the Empire — the reflective and questioning author (Socratic dialogue) were found. The question about the popsition of exclusion (M. Bakhtin) and defamiliarisation (V. Shklovsky) is raised. The novelty of the study is seen in the fact that travel stories have become at the same time a defamiliarized narrative about Russia. The conclusion is made that the semantic complex of travel in the work of A. Bitov connects the geographical (physical) and spiritual (metaphysical) spaces, that is, the external objective world and the internal spiritual and intellectual space.